Data presented in the paper "Impact of the invasive parasitic copepod Mytilicola orientalis on native blue mussels Mytilus edulis in the western European Wadden Sea" - Goedknegt, M. A. Anouk; Bedolfe, S. Sarah; Drent, J. Jan; van der Meer, J. Jaap; Thieltges, D.W. David (NIOZ Royal Netherlands Institute for Sea Research, 2018)
Research objective: Invasive species can indirectly affect native species by modifying parasite-host dynamics and disease occurrence. This scenario applies to European coastal waters where the invasive Pacific oyster (Magallana gigas) co-introduced the parasitic copepod Mytilicola orientalis that spills over to native blue mussels (Mytilus edulis) and other native bivalves. In this study, we investigated the impact of M. orientalis infections on blue mussels by conducting laboratory experiments using controlled infections with larval stages of the parasitic copepod. As the impact of infections is likely to depend on the mussels’ food availability, we also tested whether potential adverse effects of infection on mussels intensify under low food conditions. Type of research, method & collection of data: - Two replicated laboratory experiments set-up in a block design with each four treatments: infected mussel-low food condition, uninfected mussel – low food condition, uninfected mussel – high food condition (clearance rate data & condition data) - Field observational data of wild populations of mussels (condition data & infection data)